Vitamin D deficiency in the Apc(Pirc/+) rat does not exacerbate colonic tumorigenesis, while low dietary calcium might be protective - Irving, Amy A. (Dis Model Mech, 2018)
Human studies have shown that individuals with colon cancer tend to have lower serum 25-hydroxy-vitamin D(3) [25(OH)D(3)] levels compared with healthy controls, but whether this link is causative, a result of the disease or an indicator of another factor altogether has yet to be demonstrated. In humans, vitamin D, calcium and UV exposure are inextricably linked; therefore, understanding the individual and combined roles of each of these will require animal models specifically designed to address these questions. To begin to untangle this network, our group has employed the Apc(Pirc/+) rat, which contains a truncating mutation in the Apc gene, leading to the development of colonic tumors. Our group previously utilized this model to demonstrate that vitamin D supplementation above normal does not reduce colonic tumor burden and, in fact, increased tumor multiplicity in a dose-dependent manner. In the current study, we tested whether vitamin D deficiency plays a causative role in tumor development using two strains which differ in their susceptibility to intestinal tumorigenesis. In the colon, vitamin D deficiency did not increase the development of tumors in either strain, and was actually protective in one strain. Unexpectedly, low dietary calcium combined with vitamin D deficiency significantly suppressed tumor development in the small intestine and colon of both strains. The vast majority of tumors in the human intestine occur in the colon, and we find no evidence to support a direct role of vitamin D deficiency in increasing colonic tumorigenesis, and low calcium might protect against tumor development. This article has an associated First Person interview with the first author of the paper.